2017
DOI: 10.26656/fr.2017.3.025
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, mineral content and functional properties of Tarap (Artocarpus odoratissimus) seed flour

Abstract: Tarap seed (Artocarpus odoratissimus) is one of the popular snacks among Borneo Island people especially in Sabah, Malaysia. Their flesh and seed are such a potential food source but they are not fully exploited. Therefore, this study was conducted to determine its nutritional composition, mineral content and functional properties of Tarap seed flour (TSF). The proximate analysis (protein, carbohydrate, fat, crude fiber, ash, moisture), minerals content and functional properties (powder particle size, bulk den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 29 publications
(37 reference statements)
2
15
0
Order By: Relevance
“…The fat content of the JSP was 0.75%, close to the value of 0.78% (Kumar et al, 1988). The result is slightly higher than 0.4% fat reported by Sreeletha et al (2017) relatively low when compared to other Artocarpus species seed flour such as, Tarap (15.60%) and breadfruit (9.0%) seed flour (Akubor et al, 2000;Masri et al, 2017), yet still within the range of 0.13%-0.77% as reported by Ejeifor et al (2014). The relatively low-fat value suggest that the flour will be less prone to lipid-related forms of deterioration (Okpala and Gibson-Umeh, 2013).…”
Section: Proximate and Mineral Evaluation Of Jackfruit Seedsmentioning
confidence: 51%
See 3 more Smart Citations
“…The fat content of the JSP was 0.75%, close to the value of 0.78% (Kumar et al, 1988). The result is slightly higher than 0.4% fat reported by Sreeletha et al (2017) relatively low when compared to other Artocarpus species seed flour such as, Tarap (15.60%) and breadfruit (9.0%) seed flour (Akubor et al, 2000;Masri et al, 2017), yet still within the range of 0.13%-0.77% as reported by Ejeifor et al (2014). The relatively low-fat value suggest that the flour will be less prone to lipid-related forms of deterioration (Okpala and Gibson-Umeh, 2013).…”
Section: Proximate and Mineral Evaluation Of Jackfruit Seedsmentioning
confidence: 51%
“…Protein represents 13.67% of the total composition of the jackfruit seed powder in the present study. This value is higher than the protein values observed in the Artocarpus odoratissimus (8.78%), A. altilis (8.12%) and A. integer seed flour (Tukura and Obliva, 2015;Masri et al, 2017). Furthermore, the protein content reported for Mastura jackfruit cultivar seed flour was also higher than the other jackfruit clones such as J29 (7.62%), J31 (8.46%) and J33 (8.24%) seed flour samples (Azeez et al, 2015).…”
Section: Proximate and Mineral Evaluation Of Jackfruit Seedsmentioning
confidence: 55%
See 2 more Smart Citations
“…From a morphology perspective, the fruit can be regarded as an intermediate shape between the jackfruit and breadfruit. Their flesh and seed are such a potential food source but they are not fully exploited (Noorfarahzilah et al, 2017). It is reported that Tarap fruits are rich in phenolic compounds that may contribute to the health benefit when consumed (Abu Bakar et al, 2009).…”
Section: Introductionmentioning
confidence: 99%